Pricing biodiversity protection: Payments for environmental services schemes in Lao PDR. (June 2018) - Scheufele, Gabriela; Bennett, Jeff; Kyophilavong, Phouphet
Highlights: Development and application of a PES scheme that mimics market processes. Linking information on demand, supply and environmental production processes. Determination of 'efficient' prices negotiated through agent intervention. Abstract: A failure of markets to coordinate demand with supply indicates that the transaction costs of an exchange outweigh the benefits that buyers and suppliers expect to gain from trade. As a result, some goods and services are not traded in markets, despite potential demand and prospective supply. This is the case for some environmental services that exhibit the public good and common pool resource characteristic of non-excludability caused by the prohibitive transaction costs associated with defining, defending, and trading property rights over them. Payment for Environmental Services (PES) schemes are being used in an attempt to facilitate the operation of markets. However, few PES schemes involve the 'negotiation' of prices based on comparable estimates of demand and supply. This paper reports on two applications of a PES scheme design that mimics market processes for traded goods and services to an extent beyond existing attempts. It demonstrates how 'efficient' prices for biodiversity protection can be 'negotiated' through agent intervention and discusses the challenges encountered in the process.